Perceived cultural differences in healthcare for foreign patients visiting South Korea: tool development and measurement - Sumi Sung; Hyeoun-Ae Park (BMC, 2019)
Abstract Background We developed a 41-item tool measuring cultural differences in healthcare as perceived by foreign patients visiting South Korea. Methods The tool was tested on 256 foreign patients who visited three tertiary hospitals in Seoul, South Korea. Content validity was explored by two physicians and eight nurses working in an international healthcare department. Structural validity was tested via exploratory factor analysis and by testing two hypotheses: (1) there are perceived cultural differences between the South Korean healthcare and those of foreign patients' home countries (one-sample t-test); and, (2) Perceived cultural differences vary among language groups (analysis of variance). We also calculated Cronbach's alpha. Results The content validity index of the tool was 0.97. Exploratory factor analysis identified seven significant factors: hospital care and services, food, the healthcare system, communication, the healthcare facility, religion, and cultural values. The overall Cronbach's alpha for the tool was 0.96, indicating very high internal consistency. We found that foreign patients visiting South Korean hospitals perceived that the healthcare culture differed significantly from that of their home country. The perceived cultural differences varied significantly by language group. Conclusions Nurses can use our new tool to understand the cultural differences of foreign patients and provide them with culturally competent nursing care.